2021
DOI: 10.1007/s11214-020-00789-1
|View full text |Cite
|
Sign up to set email alerts
|

Formation of an Accretion Flow

Abstract: After a star has been tidally disrupted by a black hole, the debris forms an elongated stream. We start by studying the evolution of this gas before its bound part returns to the original stellar pericenter. While the axial motion is entirely ballistic, the transverse directions of the stream are usually thinner due to the confining effects of self-gravity. This basic picture may also be influenced by additional physical effects such as clump formation, hydrogen recombination, magnetic fields and the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…The behaviour of these debris streams, specifically how they are eventually circularised into a disc, is an extremely complex, and still unsolved, problem. The solution is believed to involve the debris streams shocking, either on themselves or on the forming disc (Bonnerot & Stone 2021). These shocks, in addition to circularising the disc material, will themselves liberate energy from the debris, and produce bright emission .…”
Section: Physical Interpretation Of Empirical Correlationsmentioning
confidence: 99%
“…The behaviour of these debris streams, specifically how they are eventually circularised into a disc, is an extremely complex, and still unsolved, problem. The solution is believed to involve the debris streams shocking, either on themselves or on the forming disc (Bonnerot & Stone 2021). These shocks, in addition to circularising the disc material, will themselves liberate energy from the debris, and produce bright emission .…”
Section: Physical Interpretation Of Empirical Correlationsmentioning
confidence: 99%
“…Our relativistic slim disk library provides a systematic, computationally efficient framework for fitting and interpreting the growing wealth of observational data. As noted in our previous papers (W20, W21), our model disks are inherently idealized, because complete, firstprinciples models for the hydrodynamic evolution of TDEs do not yet exist (see e.g., Bonnerot & Stone 2021 for a recent review).…”
Section: Effect Of N Hmentioning
confidence: 99%
“…The exact discrepancy between the intrinsic and observed TDE M BH distribution can result from many factors such as survey constraints and dusts (van Velzen 2018; Roth et al 2021). Also the disk formation, accretion, and emission processes in TDEs (Bonnerot & Stone 2021;Dai et al 2021;Roth et al 2020, respectively) can play a major role in altering the observed TDE M BH distribution. For example, recent hydrodynamics simulations on TDE disk formation show that not all TDEs can form circular disks efficiently through stream self-crossings (see review by Bonnerot & Stone 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Also the disk formation, accretion, and emission processes in TDEs (Bonnerot & Stone 2021;Dai et al 2021;Roth et al 2020, respectively) can play a major role in altering the observed TDE M BH distribution. For example, recent hydrodynamics simulations on TDE disk formation show that not all TDEs can form circular disks efficiently through stream self-crossings (see review by Bonnerot & Stone 2021). In particular, Shiokawa et al (2015) show that in the case of inefficient disk circularization, the accretion onto SMBHs will happen on timescales much longer than the fallback timescale, which can lower the possibility of the detection of such events.…”
Section: Introductionmentioning
confidence: 99%